2013
DOI: 10.1371/journal.pone.0062987
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of a Novel Metal-Dependent D-Psicose 3-Epimerase from Clostridium scindens 35704

Abstract: The noncharacterized protein CLOSCI_02528 from Clostridium scindens ATCC 35704 was characterized as D-psicose 3-epimerase. The enzyme showed maximum activity at pH 7.5 and 60°C. The half-life of the enzyme at 50°C was 108 min, suggesting the enzyme was relatively thermostable. It was strictly metal-dependent and required Mn2+ as optimum cofactor for activity. In addition, Mn2+ improved the structural stability during both heat- and urea-induced unfolding. Using circular dichroism measurements, the apparent mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…Among them, d-tagatose 3-epimerase (DTEase) from Pseudomonas cichorii ST-24 [28], DTEase from Rhodobacter sphaeroides [29], and l-ribulose 3-epimerase (LREase) from Mesorhizobium loti [30] showed the optimum substrate as d-tagatose, d-fructose, and l-ribulose, respectively, and other enzymes showed the optimum substrate as d-psicose and were called d-psicose 3-epimerases (DPEase), including the ones from A. tumefaciens [31], C. cellulolyticum H10 [23], C. scindens ATCC 35704 [26], C. bolteae ATCC BAA-613 [24], Clostridium sp. BNL1100 [32], Desmospora sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, d-tagatose 3-epimerase (DTEase) from Pseudomonas cichorii ST-24 [28], DTEase from Rhodobacter sphaeroides [29], and l-ribulose 3-epimerase (LREase) from Mesorhizobium loti [30] showed the optimum substrate as d-tagatose, d-fructose, and l-ribulose, respectively, and other enzymes showed the optimum substrate as d-psicose and were called d-psicose 3-epimerases (DPEase), including the ones from A. tumefaciens [31], C. cellulolyticum H10 [23], C. scindens ATCC 35704 [26], C. bolteae ATCC BAA-613 [24], Clostridium sp. BNL1100 [32], Desmospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…The metal ion remarkably increases the thermostability of the DPEases from Clostridium bolteae ATCC BAA-613 [24] and Ruminococcus sp. 5 1 39BFAA [25], and significantly improves the structural stability during heat-induced unfolding process of Clostridium scindens ATCC 35704 [26]. In addition, Choi et al has reported the I33L-S213C double-site variant of Agrobacterium tumefaciens DPEase showing significantly improved thermostability compared with the wild-type enzyme [27].…”
Section: Introductionmentioning
confidence: 99%
“…ST-24, Agrobacterium tumefaciens, Rhodobacter sphaeroides SK011, Clostridium cellulolyticum H10, Clostridium scindens 35704, Clostridium bolteae, Treponema primitia ZAS-1, Ruminococcus sp., Mesorhizobium loti, Desmospora sp, and Clostridium sp. have been characterized and employed for d-psicose synthesis [9,11,12,20,21,32,33,[36][37][38][39][40]. DTEases from A. tumefaciens, C. cellulolyticum H10, C. scindens 35704, C. bolteae, T. primitia, Ruminococcus sp., Desmospora sp, and Clostridium sp.…”
Section: Introductionmentioning
confidence: 99%
“…D-Sorbitol can be industrially produced from D-glucose, with theoretically 100 % yield by simple chemical hydrogenation (Zhang et al 2013a). L-Sorbose production was firstly reported by Reichstein et al, stating that L-sorbose could be biotechnically synthesized by oxidation of D-sorbitol using Gluconobacter oxydans (previously called Acetobacter suboxydans) pyrroloquinoline quinone (PQQ) enzymes (Reichstein et al 1933).…”
Section: Entrances To Form L-hexoses From D-hexosesmentioning
confidence: 99%